Are the Central European Stock Markets Still Different? A Cointegration Analysis - Linda Rousova (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2009)
The Central European countries became members of the European Union (EU) in May 2004. Has their accession into the EU also resulted in a stronger financial integration with the global economy in general and with the "old" EU countries in particular? Based on a cointegration analysis applied to stock market movements, I detect for the period after the EU enlargement two new long-run equilibrium relations that indeed suggest a stronger inter-dependence of the markets, whereas no such relations can be observed before this date. In particular, one new relation links the Central European markets to the Western European market, reflecting tighter co-movements of the "new" and the "old" EU markets. The second relation points at the role of the US market for both the Central and the Western European markets.
urn:nbn:de:bvb:19-epub-10993-8
Keywords: C5; F36; G11; G15; 330; Transition Economies; Emerging stock markets; Central Europe; European integration; Cointegration; Long-run stock market linkages; Aktienmarkt; Internationaler Finanzmarkt; Marktintegration; Kointegration; Schätzung; EU-Mitgliedschaft